Overeducation and happiness in the Malaysian graduate labour market - Lim, Hock Eam (Universiti Malaysia Sarawak, 2013)
The objective of this paper is to examine overeducation among Malaysian graduates with focus on its association with predetermined (before they enter the labour market) and current level of overall life happiness.Results reveal that there are a substantial percentage of overeducated graduates.Graduates who reported a higher level of predetermined happiness are less likely to be overeducated. Overeducation is also significantly and negatively associated with one’s current level of happiness.This finding suggests ‘hysterias’ of overeducation and supports Job Competition Theory’s prediction on persistent of overeducation.Thus, happiness might be one of the reasons why overeducation is a persistent and durable phenomenon.